The role of ginseng extracts green nanoparticles as an antioxidant on physiological parameters and fertility in male rats exposed to potassium dichromate - MOHAMMED A. HAMZA; MAYADA S. HASSAN; RANA F. MOUSA (Smujo International, 2024)
Abstract. Hamza MA, Hassan MS, Mousa RF. 2024. The role of ginseng extract green nanoparticles as an antioxidant on physiological parameters and fertility in male rats exposed to potassium dichromate. Nusantara Bioscience 16: 219-227. The toxicity of chrome ions is prevalent due to their commonly used in the industry. Some plants are useful for treating toxicity, and ginseng is one of the most known medicinal herbs worldwide and possesses numerous health benefits. The present study aims to use ginseng extract and nano ginseng particles to treat toxicity by potassium dichromate PDC in a rat's model. Therefore, the PDC-toxified rats were treated with ginseng extract and ginseng-NPs at different concentrations, and ginseng-NPs were prepared using green biosynthesis. ELISA technique was used for serum estimation of GSH, SOD, MDA, LH, FSH, and testosterone in the animals' groups. Ginseng extract and ginseng nanoparticles could alleviate the toxic effects of PDC, as indicated by lower MDA, higher levels of antioxidants (SOD and catalase), FSH, and LH-Ab compared to the PDC intoxication group. The results display the lower toxicity of MDA and Catalase parameters compared to groups 2 and 5, whereas the other parameters indicate an increase. By buffering the concentrations of the tested biomarkers in a concentration-dependent way, the nanoparticles added to the protective effects of ginseng. For PDC, ginseng extract has antioxidant and antitoxic properties. Using ginseng nanoparticles led to a concentration-dependent increase in the activity of ginseng extract.